Implementasi Lean Canvas Sebagai Upaya Meningkatkan Skill Enterpreneurship Mahasiswa Di Perguruan Tinggi - Suharto, Suharto (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2022)
The fundamental problem in this research is the low entrepreneurial skills of STKIP PGRI Nganjuk students amid the development of startups in Indonesia. The purpose of this research is, of course, to improve student entrepreneurship skills through the application of lean canvas. This study uses a quantitative descriptive method. The research subjects are students who own startups at STKIP PGRI Nganjuk. The number of startups studied was 50 students who already have startups in various business fields such as food and beverage products, cultivation, and services. The data collection method uses a questionnaire, observation sheet, and a final report on student startups. Data analysis using paired t-test. The results showed that the lean canvas model really helped make it easier for students to start and develop businesses. From the application of the lean canvas business model, there was an increase in student entrepreneurship skills by 8.99%.